Ursodeoxycholic Acid at 18–22 mg/kg/d Showed a Promising Capacity for Treating Refractory Primary Biliary Cholangitis - Xinyu Xiang; Xiaoli Yang; Mengyi Shen; Chen Huang; Yifeng Liu; Xiaoli Fan; Li Yang (Canadian Journal of Gastroenterology and Hepatology)
Aim. To compare the response between the current recommended dosage 13–15 mg/kg/d and 20 mg/kg/d dose of ursodeoxycholic acid (UDCA) in primary biliary cholangitis (PBC) patients who do not respond completely to a standard dose of UDCA. Methods. We included 73 patients with poor response and randomized them into two groups to investigate whether increasing the dosage of UDCA was beneficial to nonresponders. Patients assigned to the 13–15 mg/kg/d group continued with standard therapy, and participants in the 18–22 mg/kg/d group switched to the higher dosage (18–22 mg/kg/d), with a follow-up of 12 months for both groups. The primary endpoints were the rate of response at 6 months and drug side effects. Results. According to the Paris 2 criteria, patients receiving 18–22 mg/kg/d UDCA achieved a response rate of 59.4% compared with 36.1% in the standard dosage group (P=0.046) at 6 months, respectively. At 12 months, the high-UDCA-dosage group achieved a response rate of 59.4% compared with 47.2% in the standard dosage group (P=0.295), respectively. Additionally, the risk score predicted by the UK-PBC model was lower in high-dosage UDCA-treated patients than in the standard dosage group (all P<0.05). Side effects include diarrhea, nausea and vomiting, rash, and newly developed high blood pressure, which were mild and tolerated. Conclusions. Patients treated with the high UDCA dosage showed some advantages over those who continued the standard dosage in terms of biochemical remission and disease progression, indicating that standard therapy with UDCA for 6 months and then another 1 year with high UDCA dosage for nonresponders could be a treatment option before second-line therapy is recommended.